2015
DOI: 10.5937/aaser1540107s
|View full text |Cite
|
Sign up to set email alerts
|

Fruit characteristics of some traditional pear varieties in the Prespa region

Abstract: Abstract:The aim of this study was the evaluation of phonological,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The lowest coefficient of variation was observed for fruit length (12.67%). Similar studies have shown high morphological variation in pear (Pereira-Lorenzo et al, 2012;Selamovska et al, 2015).…”
Section: Quantitative Fruit Traitssupporting
confidence: 80%
“…The lowest coefficient of variation was observed for fruit length (12.67%). Similar studies have shown high morphological variation in pear (Pereira-Lorenzo et al, 2012;Selamovska et al, 2015).…”
Section: Quantitative Fruit Traitssupporting
confidence: 80%
“…The most commercial genotypes are: ʽGenotype 10ʼ (7.95 g) and ʽGenotype 5ʼ (9.24 g). Selimovska et al [2015] examined the local pear varieties (Pyrus communis L.) in West Macedonia, which showed the variation of fruit weight in the range of 13.8 g to 214.1 g, and Đurić et al [2015] examined the fruit weight of local pear varieties (Pyrus communis L.) in north-western part of Bosnia and Herzegovina, and concluded that it ranged from 31.1 to 109.4 g.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the interviews with respondents, many trees were over 80 years old. Investigated varieties derived from the same ancestor, P. communis L. according to the studies conducted in the neighbourhood area (Gasi et al 2013;Dajic ´-Stevanovic ´et al 2014;Selamovska et al 2015;Mratinic ´2000).…”
Section: Diversity Of Pyrus Varietiesmentioning
confidence: 99%